Adult attention deficit/hyperactivity disorder in the ambulatory care setting. Issue 8 (August 2020) - Hackett, Adanna; Joseph, Rose; Robinson, Kevlin; Welsh, Jeremy; Nicholas, Joyce; Schmidt, Eric
Abstract : ABSTRACT: Adult attention deficit/hyperactivity disorder (ADHD) is a significant and prevalent disorder. ADHD can impair adults' quality of life, so clinicians in multiple specialties should be able to recognize and treat the disorder. Much of the current literature has focused on childhood ADHD. However, adult ADHD is a common comorbidity in patients with mental illness, and it is essential that patients diagnosed with the disorder are treated appropriately, which can significantly improve outcomes. Adults with untreated ADHD are more likely to have substance dependence, job instability, and an overall poorer quality of life. This article reviews the screening and assessment for adult ADHD along with pharmacologic and nonpharmacologic recommendations for the management of the disorder.